Effects of whole raw soybean or whole cottonseed on milk yield and composition, digestibility, ruminal fermentation and blood metabolites of lactating dairy cows - De Almeida, Gustavo Ferreira; Del Valle, Tiago Antônio; De Paiva, Pablo Gomes [UNESP]; De Jesus, Elmeson Ferreira [UNESP]; Barletta, Rafael Vilella; Gandra, Jefferson Rodrigues; Bettero, Vitor Pereira [UNESP]; Takiya, Caio Seiti; Rennó, Francisco Palma (CSIRO Publishing, 2017)
The aim of the present study was to evaluate effects of partial replacement of corn grain and soybean meal with whole raw soybean or whole cottonseed on milk yield and composition, digestibility, ruminal fermentation and blood metabolites. Eighteen multiparous Holstein cows (133.0 ± 53.1 days in milk, 585.2 ± 54.2 kg of BW and 32.22 ± 5.32 kg/day of milk) were used in six 3 × 3 Latin squares with 21-day periods. The cows were randomly assigned to receive one of the following diets: control (CT), diet without oilseed inclusion; whole soybean (WS), inclusion of 120 g/kg of whole raw soybean (diet DM basis); and whole cottonseed (WCS), inclusion of 120 g/kg of whole cottonseed (diet DM basis). Dietary supplementation with WS or WCS had no effect on milk yield and composition. DM and non-fibre carbohydrate intake were decreased in cows fed WS and WCS when compared with CT; however, WS and WCS increased ether extract intake and digestibility. The WCS decreased DM, crude protein, ether extract and non-fibre carbohydrate intake when compared with WS. Cows fed WCS had higher ruminal pH than those fed WS or CT. Cows fed WS showed higher propionate concentration than cows fed WCS. Ruminal ammonia nitrogen concentration decreased when cows were fed WS compared with those fed CT or WCS. The partial replacement of corn grain and soybean meal with WS or WCS in diets of mid-lactating dairy cows decreased DM intake and altered ruminal fermentation, but did not affect milk yield and composition.
Keywords: cottonseed; fatty acid; linoleic acid; total tract digestion; whole soya bean